Seed Dormancy Breaking of Sugar Palm (Arenga pinnata Wurmb Merr) with Sanding and Submersion in various Concentration of Potassium Nitrate (KNO3) - Nurul Chaerani (Jurnal Biologi Tropis, 2023)
Sugar palm (Arenga pinnata) is one of the non-timber forest product that has many benefits and still had high economic demands, therefore it is necessary to be cultivated and due to the farmers still utilizing sugar palm stands that grow naturally. The cultivation of sugar palm is so difficult to be done because there was no efficient and effective technology that can break the dormancy problem yet. The objective of this research was to determine the effect of sanding and seeds submersion in various concentration of KNO3 to break the dormancy of sugar palm seeds. The experiment was performed in Greenhouse of Agriculture Faculty of Mataram University from June to September 2015. The experiment was conducted in 2x3 factorial experiments on Completely Randomized Design (CRD) with five replications. First factor was sanding (A):  A1 = without sanding dan A2 = sanding and second factor was submersion in various concentration of KNO3 (N): N1 = 0.4%, N2 = 0.5%, and N3 = 0.6%. Results of this study indicated that both treatments gave significant effect in breaking the dormancy of sugar palm seeds. Sanding and submersion in 0.5% KNO3 resulted in single significant effect on all parameters except embryonic axis. The interaction between both treatments only showed significant effect on rotten seeds.